HETEROSIS AND COMBINING ABILITY FOR YIELD AND ITS CONTRIBUTING TRAITS OF KHARIF MAIZE (ZEA MAYS L.) - RISHAV KUMAR,; SHYAM SUNDER MANDAL,; AMIT KUMAR MISHRA,; SMRITI,; RAHUL SINGH,; PAWAN KUMAR, (The Bioscan, 2015)
36 crosses were made using line x tester involving 9 lines and 4 testers which were evaluated along with two checks, namely DHM-117 and BIO-9637. Analysis of variance exhibited highly significant differences among themselves for all the traits under study. SCA was more pronounced than variance due to GCA for all the characters under study except leaf rolling. Some of the crosses found good for yield on the basis of morphological data were P 6 x P 11 (5319.66 Kg ha -1 ), P 8 x P 11 (5000.33 Kg ha -1 ), P 1 x P 13 (4906.33 Kg ha -1 ), P 7 x P 12 (4891 Kg ha -1 ) and P 9 x P 12 (4804 Kg ha -1 ). On the basis of mean performance, heterosis and SCA for grain yield total five crosses were selected and recommended for further use in our conditions